New Mediterranean Biodiversity Records (July 2018) - CHARTOSIA, NIKI; ANASTASIADIS, DIMITRIS; BAZAIRI, HOCEIN; CROCETTA, FABIO; DEIDUN, ALAN; DESPALATOVIĆ, MARIJA; DI MARTINO, VINCENZO; DIMITRIOU, NIKOS; DRAGIČEVIĆ, BRANKO; DULČIĆ, JAKOV; DURUCAN, FURKAN; HASBEK, DENIZ; et al. (Mediterranean Marine Science, 2018)
In the present article, new records are given for 15 species (4 native and 9 alien and 2 cryptogenic), belonging to 6 Phyla (i.e. Chlorophyta, Ctenophora, Cnidaria, Mollusca, Arthropoda, and Chordata), from 10 Mediterranean countries: Morocco: the finding of the crab Callinectes sapidus represents the westernmost one of the species in the Mediterranean; Italy: first records of the nudibranch Polycera hedgpethi from the harbour of La Spezia, and first finding of the invasive ctenophore Mnemiopsis leidyi in the Fiora River; Tunisia: Caulerpa taxifolia var. distichophylla is recorded for the first time, showing an even wider distribution in the Mediterranean; Greece: the finding of the jellyfish Pelagia benovici represents the first record of the species in the Ionian Sea, while the finding of the smallscale codlet Bregmaceros nectabanus in the Ionian Sea is another interesting first report for the area; Malta: the cryptogenic scleractinian coral Oculina patagonica was recorded; Slovenia: the parasitic copepod Demoleus heptapus was recorded from a sixgill bluntnose shark, Hexanchus griseus; Croatia: the Lessepsian cephalaspidean mollusc Haminoea cyanomarginata is recorded for the first time from the area; Bulgaria: the Asian date mussel Arcuatula senhousia was recorded from the Black Sea; Cyprus: the Lessepsian gastropod Viriola sp. [cf. corrugata) was recorded for the first time from the area, while two decapod species were recorded also for the first time from Cyprus, i.e. the caridean shrimp Pasiphaea sivado and the anomuran Munida curvimana; Turkey: the acari Lohmannella falcata is recorded for the first time from Antalya and the Lessepsian fish Priacanthus sagittarius in the Levantine coasts of Turkey (off Hatay/Arsuz) showing that this species has extended its range in a very short time.